PERAN WALI KELAS DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 (Studi Kasus pada SD Kanisius Sidowayah 02 Klaten) - Rizkiandani, Windy; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
The Homeroom teacher is the person who has the first opportunity to improve the quality of learning regarding his role in fostering, guiding, and psychologically preaparing students, to be ready to participate in and carryout learning and learning activities in an effective and conducive claccroom atmosphere so that the quality of learning processes and outcomes can be achieved. The hope as a homeroom teacher in increasing student learning interest in online learning during the covid-19 pandemic is that the homeroom teacher can master technology to support online learning. The purpose of this study was to explain the role of the homeroom teacher in increasing student interest in online learning during the Covid-19 pandemic at Kanisius Elementary School Sidowayah 02 Klaten. This study uses a qualitative method. The respondents of this study were the homeroom teacher of SD Kanisius Sidowayah 02 Klaten. The number of respondents in this study was 12 people. From the results of this study, the homeroom teachers of SD Kanisius Sidowayah 02 Klaten understand their respective roles increase students interest in learning.